On Strong - Dina Ameer Basheer hadid (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
In this paper we study a definition of SF – rings over strongly γ - regular rings and we find some properties and main results for it by adding some conditions. Moreover, we continue to study SPF-rings over strongly γ - regular ring and we discuss several properties for it..